Autoestima y ansiedad en padres divorciados - Navarrete Avilez, Ligia Luzmila (2018)
Low self-esteem and anxiety are fed back thanks to an essential ingredient: insecurity. Insecurity is the common denominator of low self-esteem and anxiety. We feel insecure because we do not value ourselves, because we believe that we are inept, because we have low self-esteem. And that state generates great anxiety, worsening the situation with negative and unreal thoughts. "They are going to dismiss me from work because I do everything wrong", "my partner is going to leave me because I am not worth anything" or "I will not be able to face this problem because I am weak", are some of the thoughts that cause the loss self-esteem. Because we are talking about fundamental aspects of our life, this feeling of incapacity only generates more anxiety. The anxiety problem, for whatever reason, must be treated by a professional. But to improve self-esteem we can take care of ourselves. The security in one is acquired little by little, by proposing small daily objectives and verifying that we can meet them. Some objectivity is also needed to gain security and confidence, to banish that negative vision we have and change it for a more realistic one. One of the most important impulses when it comes to eliminating insecurity is independence, turning a deaf ear to what others have to say about our lives and acting autonomously. Keep in mind that the influence of others on your safety depends on yourself, how far you want your opinion to penetrate